The Impact of Brand Image on The intention to continue using an E-Wallet Through E-Satisfaction - Fajar Suparto; Ryan Suarantalla; Syaiful Arifin (Politeknik Raflesia Press, 2025)
This study aims to analyze the influence of Brand Image on the intention to continue using E-Wallet through E-Satisfaction in West Nusa Tenggara. Using a quantitative approach, data were collected through a survey with 196 respondents who use E-Wallet. The results of the hypothesis test indicate that Brand Image has a significant positive influence on E-Satisfaction. In addition, E-Satisfaction functions as a significant mediating variable in the relationship between Brand Image and the intention to continue using E-Wallet. With a p-value smaller than 0.05, all tested hypotheses can be accepted, which confirms that E-Satisfaction strengthens the influence of Brand Image on the intention to continue using E-Wallet. These findings suggest that in order to increase E-Wallet user loyalty, companies need to build a strong brand image while ensuring a satisfying user experience.